Factors Influencing Growth of Entrepreneurial Ventures in Malaysia - Lim, Li Yen (2007)
As a developing nation, the growth of successful small-medium enterprises (SMEs) in Malaysia plays a very crucial role in the improvement of the country's economy and unemployment issues. This study is conducted to identify the success factors of founding entrepreneurs which contributes to venture growth, specifically, the relationship between venture growth and the entrepreneurs' personal initiative and human capital, the areas of competencies to be focused on, and the effectiveness of support programs provided by the government. One hundred (100) CEOs of entrepreneurial ventures are selected from the Enterprise 50 database to participate in the research through the convenient and snowballing sampling methods. Survey questionnaires are used to gather information for quantitative data, whilst qualitative data are obtained from interviews. The reliability of the questionnaire is tested using Cronbach's alpha and factor analyses are conducted to categorize the competencies. The relationships between the various constructs are examined using nonparametric statistical analysis, namely, Binary Logistics Regression, Spearman's rho, Mann-U test and Kruskal Wallis test. The study finds that there is positive significant relationship between venture growth and entrepreneurs who have personal initiative and working experience and who are focused on specific competency areas within operations, finance, and human resources. The study also discovers that there is significant negative relationship between venture growth and entrepreneurs who have high levels of education, and parents who owned business. In operations, founding entrepreneurs are found to be concerned with competitive strategies planning and the improvement of product and services. Raising capital fiom banks and institutions is the only area of concern in finance. In human resources (HR) the areas considered important are recruiting and retaining employees; HR policies and compensation plan; training and development; delegating and relinquishing control; developing performance appraisal; and motivating employees. Marketing is found to have a significant negative relationship with venture growth. The study reveals that there is no significant relationship between social network support, government support programs and venture growth.